2018
DOI: 10.3748/wjg.v24.i26.2886
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the number of examined lymph nodes on outcomes in patients with lymph node-negative gallbladder carcinoma

Abstract: AIMTo determine whether the number of examined lymph nodes (LNs) is correlated with the overall survival of gallbladder carcinoma (GBC) patients.METHODSPatients were collected from the Surveillance Epidemiology and End Results database (2004-2013) and categorized by the number of LNs into six groups: 1 LN, 2 LNs, 3 LNs, 4 LNs, 5 LNs, and ≥ 6 LNs. Survival curves for overall survival were plotted with a Kaplan-Meier analysis. The log-rank test was used for univariate comparisons.RESULTSIn a cohort of 893 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…For example, utilizing the Surveillance, Epidemiology, and End Result (SEER) database, Fan et al reported that longer survival was observed when 4 LNs were evaluated among patients with stage I disease, 4 or 5 LNs for stage II, and 6 for stage IIIA disease . Of note, the authors reported that the evaluation of 4 to 6 LNs was the optimal TLNC when examining the entire cohort ( P < 0.001) . Similarly, in the current study utilizing the NCBD, we noted that evaluate of 4 to 7 nodes was the optimal number of LNs relative to survival and staging.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…For example, utilizing the Surveillance, Epidemiology, and End Result (SEER) database, Fan et al reported that longer survival was observed when 4 LNs were evaluated among patients with stage I disease, 4 or 5 LNs for stage II, and 6 for stage IIIA disease . Of note, the authors reported that the evaluation of 4 to 6 LNs was the optimal TLNC when examining the entire cohort ( P < 0.001) . Similarly, in the current study utilizing the NCBD, we noted that evaluate of 4 to 7 nodes was the optimal number of LNs relative to survival and staging.…”
Section: Discussionsupporting
confidence: 67%
“…To the best of our knowledge, this is the first study to use a machine-learning approach to identify the optimal TLNC relative to a long-term survival among patients with GBC. 20 Of note, the authors reported that the evaluation of 4 to 6 LNs was the optimal TLNC when examining the entire cohort (P < 0.001). 20 Similarly, in the current study utilizing the NCBD, we noted that evaluate of 4 to 7 nodes was the optimal number of LNs relative to survival and staging.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Ito et al reported that survival of patients classified as N0 based on less than six LNs harvested was significantly worse than that of N0 patients based on ≥6 LNs harvested. In addition, an analysis of the Surveillance, Epidemiology, and End Result database reported that among patients with stage I, II, and IIIA disease, longer survival was observed when four LNs, four or five LNs, and six LNs were evaluated, respectively . While the recommended number of LNs to evaluate for GBC was 3 in the 6th edition of the AJCC staging manual, the most current 8th AJCC edition recommends at least six LNs be evaluated to adequately stage patients with GBC .…”
Section: Discussionmentioning
confidence: 99%